2013
DOI: 10.1097/pas.0b013e318280aa9c
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ALK-negative Anaplastic Large Cell Lymphoma With Localized Cutaneous Involvement and an Indolent Clinical Course

Abstract: Intravascular large T-cell or NK-cell lymphomas rarely present with cutaneous involvement. Intravascular cytotoxic T or NK lymphomas presenting in the skin (cIT/NKL) are often EBV, and reported cases follow a highly aggressive clinical course. Intravascular anaplastic large cell lymphoma (ALCL) by contrast is extraordinarily rare and, when it presents in the skin, raises the question of aggressive clinical behavior in the manner of cIT/NKL versus indolent clinical behavior in the manner of primary cutaneous AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 18 publications
1
39
0
1
Order By: Relevance
“…The lack of cytotoxic T-cell marker expression and clonal rearrangement of the TCR-gamma gene argues against a diagnosis of NK/T-cell intravascular T-cell lymphoma in this case. There have also been rare reports of intravascular anaplastic large cell lymphomas (ALCL) 2426 . These lymphomas express CD4 and CD30 but are ALK and EBV-negative and typically form a discrete cutaneous mass with tumor cells localized to the lymphatics.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of cytotoxic T-cell marker expression and clonal rearrangement of the TCR-gamma gene argues against a diagnosis of NK/T-cell intravascular T-cell lymphoma in this case. There have also been rare reports of intravascular anaplastic large cell lymphomas (ALCL) 2426 . These lymphomas express CD4 and CD30 but are ALK and EBV-negative and typically form a discrete cutaneous mass with tumor cells localized to the lymphatics.…”
Section: Discussionmentioning
confidence: 99%
“…D2-40 immunohistochemical analysis was performed as previously described. 6 For CD30 + TLPDs with sufficient available formalin-fixed paraffin-embedded tissue, fluorescence in situ hybridization for rearrangements involving DUSP22-IRF4 locus at 6p25.3 was performed as previously described (Mayo Clinic, Rochester, MN) 21 using a DUSP22 FISH probe produced as described. 26 Statistical analysis was performed using StatPlus:mac, version 2009 (AnalystSoft, Alexandria, VA).…”
Section: Methodsmentioning
confidence: 99%
“…13,14 An analogous T-cell entity has been described in case series of intravascular cytotoxic, often EBV + NK/ T-cell lymphomas presenting in the skin with an aggressive clinical course. 15,16 The non-ALCL intravascular NK/T-cell lymphomas [15][16][17][18][19][20] involve blood vessels 6 and show highly aggressive clinical behavior. We are left with the question of whether a subset of intravascular T-lymphoproliferative disorders presenting in the skinspecifically those with the morphologic and immunohistochemical findings of ALK À ALCL or other CD30 + TLPDs and without evidence of systemic involvementmay represent part of the spectrum of primary cutaneous ALCL and lymphomatoid papulosis rather than cutaneous manifestation of systemic disease.…”
mentioning
confidence: 99%
“…In fact, it has been demonstrated that most IVLBCL develop and grow within the lumen of blood vessels at a variance with intravascular large cell lymphomas with the T or NK phenotype. The latter have been shown to occur preferentially within lymphatic vessels, which could be differentiated from the hematic ones by virtue of their selective endothelial reactivity for podoplanin [5]. This property of IVLBCL may aid in explaining why the involvement of lymph nodes is not very frequent.…”
mentioning
confidence: 99%